Seismic vulnerability assessment of base isolated liquid storage tanks under near-fault ground motions. (September 2022) - Farajian, Mostafa; Saeed, Nariman; Kang, Won-Hee
Abstract: This paper aims to develop the fragility curves of base isolated liquid storage tanks under near-fault ground motions. Liquid storage tanks are important lifeline structures for industrial plants, but the damages from the past earthquakes showed their vulnerability. The seismic isolation technique is a promising approach to reduce the seismic demand in liquid storage tanks. It should be considered that near-fault ground motions can damage base-isolated liquid storage tanks due to their characteristics such as pulses in their time history velocity. Therefore, it is important to assess the vulnerability of the liquid storage tanks under near-fault ground motion. Fragility curves are useful tools for structural engineers to evaluate seismic performance of structures. In this study, two types of liquid storage tanks, i.e., broad and slender, are considered. The fragility curves for both non-isolated tanks and base-isolated tanks by Friction Pendulum System are developed and compared. Six failure criteria have been considered for the fragility curves, including vertical displacement of convective mass, elastic buckling of tank wall, yielding of anchorages, elephant foot buckling, pipe-line fracture and base isolation displacement. Furthermore, the effect of the isolation period and the coefficient of friction on the fragility curves are investigated. The results show that the pipeline fracture and the tank's wall buckling are the two most important parameters, which govern the behaviour of liquid storage tanks.